Website sebagai Media Pemasaran Produk-Produk Unggulan UMKM di Kota Semarang - Kristiyanti, Mariana; Rahmasari, Lisda (Universitas Brawijaya, Indonesia, 2015)
Micro, Small and Medium Enterprises (UMKM) at Semarang expands fastly. A lotof business create larger job opportunity in order to reduce unemployment people. One of theidea on empowering UMKM in information technology era is by establishing central communicationof UMKM based on Website. By making web marketing media, besides it providesinformation about UMKM development in Semarang, it can be functioned to access forany information of production factors. In addition, it can communicate with another UMKMglobally to extend the networks. Web design method uses flowchart system, while its research objectis UMKM which still run its business actively in Semarang. The resulting web is very interactive,it is because the two ways communication between the customer and UMKM, therefore it can buildcustomer community to encourage for purchasing the products in which marketed through web.